Using Electronic Worksheet in Teaching Hortatory Exposition Text Material for the 11th-Grade Students - Amalyasari, Maya Rizki; Armaditya, Marsha Firio (UIBU, 2023)
In this research, the researcher developed a teaching material that was an E-LKPD. The subject of the research was 11th-grade or 2 senior high school students. The research and development method was taken on the English subject, in the 2022/2023 school year. The research aimed to create E-LKPD teaching resources for hortatory exposition writing using Liveworksheets. Along with technology development, LKPD evolved into printed teaching material that could be presented in electronic media. The teacher gave the students an assignment with an ordinary LKPD. So that, the students felt bored. Therefore, the researcher decided to make an LKPD that was communicative, interactive, and easy to access by both students and teachers. The researcher used research and development developed by Borg and Gall and modified by Khairani. There were six phases in this research, as follows (1) preliminary study (2) product planning (3) preliminary product development (4) validation by material and media experts (5) experiment by an English teacher, and (6) final product revision and development.